Pengembangan multimedia pembelajaran interaktif kompetensi dasar pemasangan sistem penerangan dan wiring kelistrikan di SMK - Nopriyanti Nopriyanti; Putu Sudira (Jurnal Pendidikan Vokasi, 2015)
Penelitian ini bertujuan untuk: (1) menghasilkan multimedia pembelajaran interaktif kompetensi dasar pemasangan sistem penerangan dan wiring kelistrikan; (2) mengetahui kualitas multimedia pembelajaran interaktif; dan (3) mengetahui efektifitas multimedia pembelajaran interaktif kompetensi dasar pemasangan sistem penerangan dan wiring kelistrikan pada kelas XI SMK bidang keahlian Teknik Kendaraan Ringan. Penelitian ini merupakan penelitian dan pengembangan. Validasi multimedia dilakukan oleh ahli materi dan ahli media. Subjek uji coba penelitian ini adalah 32 siswa kelas XI SMKN 2 Depok, Sleman, Yogyakarta bidang keahlian Teknik Kendaraan Ringan. Kesimpulan dari penelitian ini adalah: (1) produk multimedia pembelajaran interaktif kompetensi dasar pemasangan sistem penerangan dan wiring kelistrikan layak digunakan; (2) kualitas multimedia interaktif ini sangat baik, hasil penilaian ahli ditinjau dari pembelajaran 66 (baik), isi sebesar 54 (baik), aspek tampilan 97 (baik), dan program 50 (baik), sedangkan hasil dari penilaian peserta didik uji coba lapangan pada aspek pembelajaran1277 (sangat baik), isi 1195 (sangat baik), tampilan 1562 (sangat baik), dan pemograman 519 (sangat baik); (3) Produk multimedia pembelajaran interaktif kompetensi dasar pemasangan sistem penerangan dan wiring kelistrikan efektif meningkatkan hasil belajar siswa. Rata-rata penilaian hasil belajar siswa ketika pretest adalah 63,75 dengan nilai terendah 50 dan nilai tertinggi 75. Sedangkan rata-rata nilai posttest sebesar 78,75 dengan nilai terendah 65 dan nilai tertinggi 90. DEVELOPING INTERACTIVE LEARNING MULTIMEDIA THE BASIC COMPETENCY IN INSTALLING LIGHTING AND ELECTRIC WIRING SYSTEMS AT VOCATIONAL SCHOOLSAbstractThis study aims to: (1) develop an interactive learning multimedia the basic competency in installing lighting and electric wiring system; (2) describe an the quality of the interactive learning multimedia; and (3) describe the effectiveness of the interactive learning multimedia the basic competency in installing lighting and electric wiring system for Grade XI students of the Light Vehicle Engineering expertise competency program at SMK. This was a research and development (R & D). The validation of the multimedia by a matterial expert and media expert. The tryout subjects in the study were 32 people Grade XI students of the Light Vehicle Engineering expertise competency program at SMKN 2 Depok. The conclusions of the study are as follows. (1) the interactive learning multimedia product for the basic competency in installing lighting and electric wiring systems is appropriate to be used for learning grade XI SMK. (2) the assessment of the material expert and media expert on instructional learning multimedia show that the learning aspect attain a score of 66 (good), the content aspect attains a score of 54 (good), the display aspect attains a score 97 (good) and the aspect attains a score of the 50 (good) while the students' assessment from the field tryout conducted at SMK Negeri 2 Depok shows that the learning aspect attains a score of 1277 (very good), the content aspect attains a score of 1195 (very good), the display aspect attains a score of 1562 (very good), and the programming aspect attains a score of 519 (very good); (3) the developed product is effective to improve the student learning outcomes. This is indicated by the result of the pretest and posttest analysis. The Average assessment of learning outcomes when the pretest of 63,75, with the lowest score of 50 and a highest of 75. While the average score posttest of 78,75 with the lowest score of 65 and the highest score of 90.